Az innovációk térbeli terjedése a magyar mezőgazdaságban - Enyedi, György; Rechnitzer, János (Tér és Társadalom, 1987)
The paper presents the results of a study on the diffusion of an agricultural innovation, the production system, over the territory of Hungary. The objective of the investigations was to establish the temporal and Spatial regularities of innovation diffusion and to compare them with the models developed by Högerstrand's disciples. Production systems have spread in the Hungarian agriculture from the beginning of the 1970s. The essential features of a production system are as follows: the model farm or innovator elaborates a detailed and precise technology, similar to an industrial one, for the production of some produce. It introduces this on payment of a fee in a large-scale farm, which is willing to accept the programme, and controls its putting into practice, provides the farm services and thereby guarantees a high output. This entire innovation chain has remained within the Hungarían agricultural sector; research and development as well as marketing are done by the model state- or cooperative farms, the so called system-masters. In 1985 there were 64 production systems operating in the Hungarian agriculture, 20 in field crop production, 22 in animal husbandry and 22 in gardening. 89 percent of the wheat, 91 percent of maize, 96 percent of sugar beat, 89 percent of eggs of large-scale farms were produced in production systems. Eight systems had more than 200 member-farms. Most of the systems, however, operated with only 10-15 members. The present paper examines the spatial diffusion of two maize production systems between 1971 and 1981. The first system, abridged as IKR in Hungarian, was introduced by the Bábolna State Farm in 1971 and by 1981 it counted 260 member-farms. The second, named KITE, was formed in 1982 under the auspices of the Vörös Csillag (Red Star) Agricultural Cooperative of Nádudvar. The research findings: 1. The diffusion of both production systems had three distinct stages: the period of take-off up to 1975; the period of propagation (1975-1980); and the state of saturation following 1980. The IKR is present in each of the 19 counties of Hungary, KITE has no member-farms in four West-Hungarian counties. The spatial extent of IKR varied more widely (e.g. in 1977 it was sharply reduced due to a drop in profitability) than that of KITE which had a relatively even diffusion with some concentration on the loess ridges of the Alföld (the Great Hungarian Plain). 2. The role of distance in the propagation of the production systems was studied and in this respect the question was raised if the diffusion was spatially contiguous or not. First a fairly concentrated hard core formed around the settlement where the model farm is situated. New memberfarms at considerable distances only appeared in a scattered way, in the period of propagation. An analysis of the centre of gravity was made to identify the direction of diffusion of both systems, by counties and for the country as a whole. In the period of take-off the centre of gravity of the IKR system was in Komárom county where the model farm is located (Bábolna). Then it moved swiftly eastward indicating the rapid expansion of the IKR in the Alföld. In the period of propatagion, the direction of diffusion changed, the centre of gravity got closer to Transdanubia again, indicating the exodus of the system from North-Hungary. The centre of gravity of KITE followed a smoother path. In the beginning, from the time the system appeared in West-Alföld and in Transdanubia, it moved westwards. Later the movement slowed down and remained within the same region. 3. The member-farms of the two systems were classified in a cluster analysis with regard to the spatial characteristics of the diffusion. The following groups were identified: (1) farms which were innovators and promoted the innovation diffusion; (2) centres of local innovation transmission; (3) farms which joined the system with large fields in the period of take-off and remained stable members; (4) farms which are similar to the previous group but which later reduced their areas involved significantly; (5) farms which are located far from the model-farms and which joined systems at the end of the take-off period; (6) the 'marginal' farms of the production systems: they entered the system with a small arca, some left then re-entered etc. The analysis has proved that the spatial regularities of innovation diffusion can be modellized; the process of innovation diffusion in a planned economy is similar to that in a marked economy in case of autonomous entrepreneur decisions and profit orientation.